Water mites of the family Torrenticolidae Piersig, 1902 (Acari: Hydrachnidia) from Thailand, Part I. The genera Torrenticola Piersig, 1896, Neoatractides Lundblad, 1941 and Pseudotorrenticola Walter, 1906 - Pesic, Vladimir; Smit, Harry (Zootaxa, 2009)
New records of water mites of the genera Torrenticola Piersig, 1896, Neoatractides Lundblad, 1941 and Pseudotorrenticola Walter, 1906 (Acari: Hydrachnidia, Torrenticolidae) from streams in Thailand are presented. A detailed description is provided for all species of Torrenticola Piersig, 1896 and Neoatractides Lundblad, 1941. Three species new to science are described: Torrenticola siamis, T. thailandicus and T. wilesi; a first description of the male is given for T. malaisei (Lundblad, 1941). Additionally, first records from Thailand are given for Torrenticola maharashtris Cook, 1967, T. malaisei (Lundblad, 1941), T. turkestanica (Sokolow, 1926), T. tetrapora (Viets, 1935), T. sp., Neoatractides bahtilli (Wiles, 1991) and N. malayensis (Wiles, 1991).